Evaluation of Salaries and Their Factors in Lithuania - Subačienė, Rasa; Bruzdeilynaitė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2022)
Salaries and wages are widely analysed in legal, economic and social dimensions. Remuneration reflect many aspects, therefore, they play a significant role for the individual, for whom it is often the main source of livelihood, for the company, for which the compensation of the employee’s work is both business expenses and elements of business execution, and for the state, which directly influences wages through its regulatory mechanisms and for which the amount of salary is an important indicator of society’s standard of living. The purpose of the study is to evaluate the salaries forms and systems applied in Lithuanian companies and the factors affecting them. To achieve the goal, the methods of scientific literature analysis, information grouping, systematization, and generalization were applied. A questionnaire survey was conducted in Lithuania in order to assess the forms and systems of salaries and the factors affecting them. The results of the study show that internal factors have the greatest influence on wages. External factors of greatest impact are the salary level in the region/country, labour market conditions, and the impact of the government. In Lithuanian companies, the time based form of salaries is most widely used, the unit based form is used in 19%, and the mixed form - in 26% of all companies. The research results show that the trends in the development of salaries’ systems are aimed at developing the employee’s individual abilities, promoting his motivation to achieve both personal and company results, compensation for the work performed on different forms, with the purpose to achieve maximum definiteness, clarity and objectivity of the systems.